A comprehensive working state monitoring method for power battery packs considering state of balance and aging correction. (15th March 2019) - Wang, Shun-Li; Fernandez, Carlos; Zou, Chuan-Yun; Yu, Chun-Mei; Chen, Lei; Zhang, Li
Abstract: A comprehensive working state monitoring method is proposed to protect the power lithium-ion battery packs, implying accurate estimation effect but using minimal time demand of self-learning treatment. A novel state of charge estimation model is conducted by using the improved unscented Kalman filtering method, in which the state of balance and aging process correction is considered, guaranteeing the powered battery supply reliability effectively. In order to realize the equilibrium state evaluation among the internal battery cells, the numerical description and evaluation is putting forward, in which the improved variation coefficient is introduced into the iterative calculation process. The intermittent measurement and real-time calibration calculation process is applied to characterize the capacity change of the battery pack towards the cycling maintenance number, according to which the aging process impact correction can be investigated. This approach is different to the traditional methods by considering the multi-input parameters with real-time correction, in which every calculation step is investigated to realize the working state estimation by using the synthesis algorithm. The state of charge estimation error is 1.83%, providing the technical support for the reliable power supply application of the lithium-ion battery packs. Highlights: A novel comprehensive state of charge estimation method for the lithium-ion battery pack. The state of balance and aging process correction is considered in the recommended method. The estimation model is conducted by using the improved unscented Kalman filter. The improved variation coefficient is introduced to evaluate the cell-to-cell consistency.